Preparation and properties of isocyanate and nano particles composite modified asphalt. (30th August 2016) - Fang, Changqing; Yu, Xin; Yu, Ruien; Liu, Pei; Qiao, Xiaoting
Highlights: Using isocyanate and nano particles as composite modifier. Samples are prepared under conditions of different addition of modifiers. The effects of nano particle on isocyanate modified asphalt properties were tested. The thermal stability of composite modified asphalt has a further promotion. Abstract: Isocyanate modified asphalt samples were got by adding quantitative isocyanate into the base asphalt. Isocyanate and nano particles composite modified asphalt samples were produced by adding quantitative isocyanate and three different kinds of inorganic nanoparticles (Silicon dioxide, Titanium dioxide, Zinc oxide) into the base asphalt respectively. Isocyanate modified asphalt, isocyanate and nanoparticles composite modified asphalt were characterized by taking physical tests, SEM, fluorescence microscopy, TG and FTIR tests, which demonstrated that the high and low temperature performance of isocyanate and nano particles composite modified asphalt had been improved effectively. From the microscopic view, the modification of the base asphalt was very significant. Results also indicated that the temperature sensitivity of composite modified asphalt had been decreased. Meanwhile, the thermal stability had been improved when compared with the base asphalt and isocyanate modified asphalt.